Studi Komparatif Kelayakan Usaha Pembuatan Dendeng Itik dengan Kerupuk Itik Di Kabupaten Hulu Sungai Utara (Studi Kasus: Usaha Pembuatan Dendeng Itik "Dhandy" dengan Kerupuk Itik "Mama Irfan" di Kecamatan Amuntai Tengah - Susanti Dewi (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
The purpose of this study is (i) identifying the non-financial feasibility of duck and duck cracker making business in terms of market, technical aspects and management aspects (ii) analyzing and (iii) comparing the financial feasibility of making duck and duck crackers in Central Amuntai District. The research was carried out on the "Dhandy" duck jerky in Antasari Village and "Mama Irfan" duck crackers in Kota Raden Hulu Village, Amuntai Tengah District, Hulu Sungai Utara Regency in May - August 2013. The research method used was case studies and data collection with interviews. Qualitative analysis of market, technical and management aspects is processed descriptively. Quantitative analysis uses investment criteria, namely analysis of present net value / NPV, return on investment / IRR, Net B / C ratio and return period of investment, the results of the two analyzes are followed by comparative analysis. The results of the non-financial aspects showed that the "Dhandy" jerky duck and "Mama Irfan" duck crackers viewed from the market or technical aspects were worth the effort. However, viewed from the management aspect, the two businesses are not feasible because they are still in the scale of small businesses, family efforts and implementation are still traditional. The financial aspect of the "Dhandy" duck jerky business is worth showing the NPV value of Rp.5,950,594, - the IRR of 12.92%, net B / C of 1.22 and the pay back period of 4,5024 years. Whereas the "Mama Irfan" duck cracker business is also worthy of the NPV value of Rp. 31,874,247, -, the IRR is 51.93%, net B / C is 2.71 and the pay back period is 2.4716 years. Comparative analysis shows that the "Mama Irfan" duck cracker making business is more feasible compared to the "Dhandy" duck jerky making business. The purpose of this study is (i) identifying the non-financial feasibility of duck and duck cracker making business in terms of market, technical aspects and management aspects (ii) analyzing and (iii) comparing the financial feasibility of making duck and duck crackers in Central Amuntai District. The research was carried out on the "Dhandy" duck jerky in Antasari Village and "Mama Irfan" duck crackers in Kota Raden Hulu Village, Amuntai Tengah District, Hulu Sungai Utara Regency in May - August 2013. The research method used was case studies and data collection with interviews. Qualitative analysis of market, technical and management aspects is processed descriptively. Quantitative analysis uses investment criteria, namely analysis of present net value / NPV, return on investment / IRR, Net B / C ratio and return period of investment, the results of the two analyzes are followed by comparative analysis. The results of the non-financial aspects showed that the "Dhandy" jerky duck and "Mama Irfan" duck crackers viewed from the market or technical aspects were worth the effort. However, viewed from the management aspect, the two businesses are not feasible because they are still in the scale of small businesses, family efforts and implementation are still traditional. The financial aspect of the "Dhandy" duck jerky business is worth showing the NPV value of Rp.5,950,594, - the IRR of 12.92%, net B / C of 1.22 and the pay back period of 4,5024 years. Whereas the "Mama Irfan" duck cracker business is also worthy of the NPV value of Rp. 31,874,247, -, the IRR is 51.93%, net B / C is 2.71 and the pay back period is 2.4716 years. Comparative analysis shows that the "Mama Irfan" duck cracker making business is more feasible compared to the "Dhandy" duck jerky making business.